Contenido de ácidos grasos en cuatro poblaciones de pejibaye, Bactris gasipaes (Palmae) - Fernández-Piedra, Mireya (1995)
Cooked and uncooked samples from four pejibaye palm races were analyzed to detenrune the moisture content, ether extract and the content of six fatty acids (C16:0 to C18:3). There was an increase in moisture and a decrease in ether extract (p<0.05) in the cooked samples in comparison with the uncooked ones. No significant differences were found in fatty acid content between cooked an uncooked samples, but there were differences (p<0.05) among races conceming the content of four fatty acids. Pejibaye fat is mainly mono-unsaturated (45.6%) and has a low poly-unsaturated to saturated fatty acid ratio (0.5). The fatty acid profile of uncooked pejibaye samples was: oleic acid, 32.6 to 47.8 %; palmitic acid, 30.5 to 40.3 %; linoleic acid, 11.2 to 21.1 %; palmiloleic acid, 5.7 lo 7.1 %; linolenic acid, 1.5 lo 5.5 %; and stearic acid, 1.7 to 2.4 %.